Kebangsaan dalam Al Quran (Studi Tematik Ayat ayat Kebangsaan Prespektif Al Mawardi) - Muhammad Nur Amin (CV. Creative Tugu Pena, 2024)
The growth of ideology is increasingly rapid and accompanied by a change of national issues, thus making humans think forward to create a solid national construction. The construction was built from two different elements, namely: religion and politics. This is in line with the idea of ??Almawardi in building a nation in accordance with the content of national verses in the Koran. In this study the researcher tried to describe the right national construction according to Almawardi. Furthermore, this study uses a qualitative approach with a type of library study (library reseach) and supported by descriptive methods, namely: Thematic method. The results of this study indicate that Almawardi has used religion as a barometer of politics of politics and a good relationship between the people (Ahlul Ikhtiyar) and the leader of the nation called Ahlul Imamat. The theory of social contracts was created to protect the articles of obligations and fulfill the rights of both. Keywords: Nationality, Qur'an, Almaward